Quality of spent hen sausages incorporated with bee honey - MS Ali; Rahman, MM; Habib, M; Kabir, MH; Hashem, MA; Azad, MAK; Rahman, MM (Meat Research, 2022)
The experiment was conducted to find out the effect of bee honey on the sensory, physicochemical and biochemical properties of spent hen sausages. For this purpose, sausages were prepared into four different groups. They were as follows: broiler breast meat sausage without bee honey, spent hen breast meat sausage without bee honey, spent hen breast meat sausage with 2% bee honey and spent hen breast meat sausage with 4% bee honey. All parameters were analyzed at 0, 15thand 30thdays of storage time. Significant differences were found in pH, the percentages of dry matter (DM), crude protein (CP) and ether extract (EE), while no significant differences were found inthe percentageof cookingloss andash of sausage batter. While analyzing the different types of sausages, CP, ash and EE content of all treatments differ significantly (p<0.05). In contrast, CP and EE content increased significantly (p<0.01), while ash content decreased significantly (p<0.01) with the advancement of different days of intervals. The FFA, POV and TBARS values were increased significantly (p<0.01) with prolonging the storage time. Lightness (L*)and yellowness (b*)did not differ among different sausages and time of intervals. Redness (a*)wassignificantly higher in broiler breast meat sausages without bee honey. Redness increased significantly with the advancement of different days of intervals.Flavor and overall acceptability were found significantly lowerin spent henbreast meat sausage without bee honey.Bee honey increased the flavor, juiciness, tenderness and overall acceptability of spent hen breast meat sausages similar to broiler breast meat sausage. Although no significant differences were found among broiler breast meat sausage without bee honeyandspent hen sausages with 2% or 4% bee honey, but overall acceptability was higher in spent hen sausages with 4% bee honey.